2014
DOI: 10.1038/ncomms6180
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Strip serves as a platform for early endosome organization during axon elongation

Abstract: Early endosomes are essential for regulating cell signalling and controlling the amount of cell surface molecules during neuronal morphogenesis. Early endosomes undergo retrograde transport (clustering) before their homotypic fusion. Small GTPase Rab5 is known to promote early endosomal fusion, but the mechanism linking the transport/clustering with Rab5 activity is unclear. Here we show that Drosophila Strip is a key regulator for neuronal morphogenesis. strip knockdown disturbs the early endosome clustering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 63 publications
6
45
1
Order By: Relevance
“…As we reported in our previous studies (Sakuma et al, 2014; Sakuma et al, 2015), one of the major roles of Strip is to regulate axon elongation. To investigate the role of Strip in synaptic development that occurred after axon elongation, we weakly knocked down strip specifically in motor neurons by using short hairpin RNA (The locations of the short hairpin RNA sequences on the strip molecular map is shown in Figure S1A).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…As we reported in our previous studies (Sakuma et al, 2014; Sakuma et al, 2015), one of the major roles of Strip is to regulate axon elongation. To investigate the role of Strip in synaptic development that occurred after axon elongation, we weakly knocked down strip specifically in motor neurons by using short hairpin RNA (The locations of the short hairpin RNA sequences on the strip molecular map is shown in Figure S1A).…”
Section: Resultssupporting
confidence: 68%
“…Using an anti-Strip antibody (Sakuma et al, 2014), we found that Strip is localized at presynaptic sites adjacent to the neuronal membrane marker, HRP. It is excluded from the muscle subsynaptic reticulum (SSR), an in-folded membranous structure that contains many components including neurotransmitter receptors and the postsynaptic signaling complex, and was identified by Spectrin labeling (Figures 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane and transmembrane proteins are transported to axon terminals via a Rab11-dependent mechanism whereas Rab5 and Rab7 are involved in local recycling and retrograde transport back to the soma (Jin et al, 2018; Khodosh et al, 2006). In Drosophila , a loss-of-function mutation in Rab5 causes defects in axon elongation in olfactory projection neurons and sensory neurons (Sakuma et al, 2014; Satoh et al, 2008). Mutations in Rab7 linked to Charcot-Marie-Tooth2b disease cause axon growth and guidance defects in fly sensory neurons (Ponomareva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%